A revision of the genus Systellantha B. C. Stone. Studies in Malaysian Myrsinaceae IV. Issue 4 (December 2015) - Drinkell, Clare; Utteridge, Timothy
Summary The genusSystellantha (Primulaceae, Myrsinoideae) is revised here; three species are recognised. One new species is described and illustrated:Systellantha serratifolia Utteridge & Drinkell sp. nov. from northern Borneo; two varieties of this species are recognisedS. serratifolia var.serratifolia andS. serratifolia var.dolichophylla Utteridge & Drinkell var. nov. A key to the genus is given, and descriptions, conservation ratings, and distribution maps provided for each species; a list of exsiccatae is supplied.